Rational engineering of a cold-adapted α-amylase from the Antarctic ciliate Euplotes focardii for simultaneous improvement of thermostability and catalytic activity - Yang G.; Yao H.; Mozzicafreddo M.; Ballarini P.; Pucciarelli S.; Miceli C. (Applied and Environmental Microbiology, 2017)
The α-amylases are endo-acting enzymes that hydrolyze starch by randomly cleaving the 1,4-α-D-glucosidic linkages between the adjacent glucose units in a linear amylose chain. They have significant advantages in a wide range of applications, particularly in the food industry. The eukaryotic α-amylase isolated from the Antarctic ciliated protozoon Euplotes focardii (EfAmy) is an alkaline enzyme, different from most of the α-amylases characterized so far. Furthermore, EfAmy has the characteristics of a psychrophilic α-amylase, such as the highest hydrolytic activity at a low temperature and high thermolability, which is the major drawback of cold-active enzymes in industrial applications. In this work, we applied site-directed mutagenesis combined with rational design to generate a cold-active EfAmy with improved thermostability and catalytic efficiency at low temperatures. We engineered two EfAmy mutants. In one mutant, we introduced Pro residues on the A and B domains in surface loops. In the second mutant, we changed Val residues to Thr close to the catalytic site. The aim of these substitutions was to rigidify the molecular structure of the enzyme. Furthermore, we also analyzed mutants containing these combined substitutions. Biochemical enzymatic assays of engineered versions of EfAmy revealed that the combination of mutations at the surface loops increased the thermostability and catalytic efficiency of the enzyme. The possible mechanisms responsible for the changes in the biochemical properties are discussed by analyzing the three-dimensional structural model.